1999
DOI: 10.1046/j.1432-1327.1999.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Molten globule‐like state of human serum albumin at low pH

Abstract: Human serum albumin (HSA), under conditions of low pH, is known to exist in two isomeric forms, the F form at around pH 4.0 and the E form below 3.0. We studied its conformation in the acid-denatured E form using far-UV and near-UV CD, binding of a hydrophobic probe, 1-anilinonaphthalene-8-sulfonic acid (ANS), thermal transition by far-UV and near-UV CD, tryptophan fluorescence, quenching of tryptophan fluorescence using a neutral quencher, acrylamide and viscosity measurements. The results show that HSA at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
87
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 45 publications
13
87
0
Order By: Relevance
“…Although the occurrence of a folding intermediate in the unfolding of HSA upon extensive glycation or lowering of pH was previously reported [52,53], this is the first evidence for a folding intermediate in heme-HSA stabilized by myristate binding. Moreover, it appears that heme binding is not crucial for the formation of the folding intermediate.…”
Section: Discussionmentioning
confidence: 46%
“…Although the occurrence of a folding intermediate in the unfolding of HSA upon extensive glycation or lowering of pH was previously reported [52,53], this is the first evidence for a folding intermediate in heme-HSA stabilized by myristate binding. Moreover, it appears that heme binding is not crucial for the formation of the folding intermediate.…”
Section: Discussionmentioning
confidence: 46%
“…In order to assimilate and release molecules of quite distinct size/shape in the circulatory system, HSA has to possess a flexible structure. This was positively inferred from changes in the solvation dynamics of HSA, using the single tryptophan fluorescence as reporter, which correlated with the conformational transitions that occur upon pH changes [30].…”
Section: Resultsmentioning
confidence: 99%
“…15 Further studies revealed that the amount of albumin that ends up being associated with micelles reached saturation at 1/1 HSA-GM1 w/w ratio and also that at 55°C and at pH 3, where HSA is reversibly denatured and exposes part of its hydrophobic residues, the interaction is favored. [29][30][31] Considering these results together and the fact that Dox might end up located in more external domains of GM1 micelles, we wondered whether the incorporation of Dox into GM1 or Ptx-GM1 micelles could have any effect on their ability to interact with HSA.…”
Section: Interaction Of Dox-gm1 and Dox-ptxgm1 Micelles With Hsamentioning
confidence: 99%